The arrival of SARS-CoV-2 in Venezuela - Paniz-Mondolfi, Alberto E; Sordillo, Emilia M; Márquez-Colmenarez, Marilianna C; Delgado-Noguera, Lourdes A; Rodriguez-Morales, Alfonso J (The Lancet (British edition), 2020)
Almost 2 years ago, after the collapse of health-care services and multiple concurrent re-emerging diseases outbreaks, the US Centers for Disease Control and Prevention issued the ongoing recommendation that travellers should avoid all non-essential travel to Venezuela.2 The arrival of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is therefore a major challenge for the country's already fragile systems. The economic collapse in Venezuela and lack of investment in health care has dramatically decreased the number of hospital beds to care for its population of almost 30 million people. The inventory of hospital beds (23 762 beds) released by the Venezuelan Government3 on March 23, 2020, overestimates availability because most public health-care centres are currently functioning under technical shutdown due to insufficient essential equipment, consumables, drug inventories, and qualified health-care professionals.